Titanium carbide thin film material, preparation method and zinc ion hybrid capacitor
The nanosheet twisting strategy forms a titanium carbide film material with super-wrinkle structure, which solves the problem of high tortuousness of MXene film under high load conditions, significantly improving its electrochemical performance and long-term stability.
Patent Information
- Application Number
- CN202510047626.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-13
AI Technical Summary
Under high load conditions, the high tortuousness of the MXene film limits its electrochemical performance. The existing researched 3D porous structure and vertically arranged MXene nanosheets are not effective when applied at the energy storage device level and are prone to collapse.
Through the nanosheet twisting strategy, the spacing between titanium carbide nanosheets is severely changed by ion exchange, forming a super-pleated structure, maintaining structural integrity and maintaining gaps between layers, which is suitable for high-pressure and high-load conditions.
It significantly reduces the tortuousness of the electrode, improves ion transfer efficiency, and improves electrochemical performance, including high surface capacitance and long-term cycle stability, meeting the needs of high-quality load applications.
Smart Images

Figure CN119446801A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a titanium carbide film material, a preparation method and a zinc ion hybrid capacitor, and belongs to the field of energy storage. Background Art
[0002] In modern energy storage technology, the development of high-load electrodes is a key factor in improving the energy density of energy storage devices such as capacitors and reducing overall costs. High-load electrodes improve the overall energy density of energy storage devices by significantly increasing the content of active materials and reducing the inactive components inside the energy storage device. However, there are a series of key challenges in the preparation of thick electrodes to achieve high loads. First, thick electrodes are prone to breakage during the drying process, which not only affects the structural integrity of the electrode, but may also cause contact failure with the current collector. With the increase in thickness, the stress and strain generated in the electrode material during the drying process increase significantly, which in turn causes cracks and interlayer separation. In addition, the conductive agent and binder in the electrode are often unevenly distributed during the coating process and are easily enriched on the electrode surface. This unevenness reduces the conductivity of the electrode and seriously affects its long-term cycle stability.
[0003] In recent years, self-supporting electrodes have been proposed as an emerging alternative. Self-supporting electrodes do not require binders, conductive agents, and current collectors, which simplifies the manufacturing process while improving the structural integrity and energy density of the electrode. Metal and carbon-based materials are often used as framework materials to support active materials to form self-supporting electrodes, thereby enhancing the transport of electrons and ions. However, in practical applications, ensuring the uniformity and consistency of the composite of framework materials and active materials remains a major challenge, especially when scaled up to industrial scale. Therefore, directly using materials that can act as both a framework and have activity is an excellent choice.
[0004] As a new type of two-dimensional material, MXenes have attracted much attention due to their excellent electrical conductivity and good ionic conductivity. However, current research mainly focuses on low loading (1-2 mg cm -2 ) has not yet met the performance improvement at high loadings (over 10 mg cm -2 ) actual needs. x Taking MXene (titanium carbide) as an example, although its conductivity is as high as 20,000 S cm -1However, under high load conditions, the close arrangement of nanosheets prolongs the ion transport path and increases the ion transport resistance, resulting in a high tortuosity of the electrode constructed therefrom, which limits its electrochemical performance. Among them, the tortuosity of the electrode is usually defined as the ratio between the actual transport distance of ions in the electrode and the straight-line distance. Therefore, the development of low-tortuosity MXene films is crucial to improving performance under high loads. Existing research based on, such as 3D porous structures and vertically arranged MXene nanosheets, although reducing the tortuosity of MXene films to a certain extent, is often limited in practical applications and is not effective when applied at the energy storage device level. Because internal pressure is inevitable during the encapsulation process of energy storage devices, this may cause the carefully designed MXene structure to collapse into a tightly stacked structure, severely limiting its performance at the energy storage device level. Therefore, there is an urgent need to develop a new electrode material that can maintain electrode structure and performance under high pressure and high load conditions. Summary of the invention
[0005] In view of the deficiencies in the prior art, one of the objects of the present invention is to provide a method for preparing a titanium carbide thin film material with a novel structure; a second object of the present invention is to provide a titanium carbide thin film material; and a third object of the present invention is to provide a zinc ion hybrid capacitor.
[0006] In order to solve the above technical problems, the technical solution of the present invention is as follows: A method for preparing a titanium carbide thin film material comprises the following steps: S1, providing titanium carbide nanosheets; S2, mixing the titanium carbide nanosheets and the aqueous solution of ammonium salt, performing ultrasonic treatment, and then performing solid-liquid separation, and taking the upper layer of liquid to obtain intercalated titanium carbide nanocolloids; Wherein, the ammonium salt is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide; S3, adding a water-soluble salt to the intercalated titanium carbide nano-colloid, and after the reaction, performing solid-liquid separation, washing with water, and drying to obtain titanium carbide aerogel; Wherein, the water-soluble salt is one or more of zinc salt, sodium salt, lithium salt, potassium salt, magnesium salt, iron salt and calcium salt; S4, compression molding the titanium carbide aerogel to obtain a titanium carbide thin film material.
[0007] Thus, the present invention uses a nanosheet twisting strategy to form a super-wrinkled structure of titanium carbide nanosheets. Specifically, ammonium ions with a larger ionic radius are first introduced during the intercalation process of the titanium carbide nanosheets, and then the ammonium ions are replaced with metal ions with a smaller ionic radius through ion exchange. Through ion exchange, the interlayer spacing of the titanium carbide nanosheets changes dramatically, thereby achieving the distortion of the nanosheets and forming a super-wrinkled structure. This structure can still maintain structural integrity and maintain the gap between layers under high pressure conditions, and has good mechanical stability. The obtained titanium carbide thin film material is applied to the electrode material of energy storage devices such as zinc ion hybrid capacitors, and it is found that the tortuosity of the electrode is significantly reduced, thereby significantly improving the ion transmission efficiency, so that the energy storage device exhibits more excellent electrochemical performance.
[0008] Optionally, the preparation method of the titanium carbide nanosheets includes the following steps: adding Ti3AlC2 to a hydrofluoric acid solution, maintaining the solution temperature at 25-40°C, reacting for 4-8 hours, and centrifugally washing with deionized water until the pH value of the supernatant is 5-6 to obtain titanium carbide nanosheets; wherein the concentration of the hydrofluoric acid solution is 20-40wt%, further 25-35wt%.
[0009] Optionally, in S2, the concentration of the ammonium salt in the aqueous solution is 5-25wt%, further 10-20wt%, further 12-18wt%.
[0010] Optionally, in S2, the ultrasonic treatment time is 30-90 min, further 45-75 min, and further 50-70 min; during solid-liquid separation, centrifugation is performed at a rate of 3000-4000 r / min for 30-90 min, and further, at a rate of 3200-3800 r / min for 45-75 min.
[0011] Optionally, in S3, an aqueous solution of a water-soluble salt is added dropwise to the intercalated titanium carbide nanocolloid, stirred for 5-45 minutes (further 10-30 minutes), washed by centrifugation with deionized water, and dried to obtain a titanium carbide aerogel; The concentration of the water-soluble salt in the aqueous solution of the water-soluble salt is 1.5-2.5 mol / L, preferably 1.8-2.3 mol / L, and the amount of the aqueous solution of the water-soluble salt added is 0.2-0.3 times the volume of the titanium carbide nanocolloid, preferably 0.22-0.28 times.
[0012] Excess water-soluble salts can be removed better by water washing, which helps to obtain purer titanium carbide aerogel.
[0013] Optionally, in S3, the drying method is freeze drying, and optionally, the freeze drying time is 40-60 hours, further 45-55 hours.
[0014] Optionally, the zinc salt is one or more of zinc sulfate, zinc chloride and zinc nitrate.
[0015] Optionally, the sodium salt is one or more of sodium sulfate, sodium chloride, sodium nitrate and sodium fluoride.
[0016] Optionally, the lithium salt is one or more of lithium sulfate, lithium nitrate and lithium chloride.
[0017] Optionally, the potassium salt is one or more of potassium sulfate, potassium nitrate, potassium chloride and potassium fluoride.
[0018] Optionally, the magnesium salt is one or more of magnesium sulfate, magnesium nitrate and magnesium chloride.
[0019] Optionally, the iron salt is one or more of ferric sulfate, ferric chloride and ferric nitrate.
[0020] Optionally, the calcium salt is one or more of calcium chloride and calcium nitrate.
[0021] Optionally, in S4, the compression molding method is cold press molding, and the molding pressure is 0.8-1.2 MPa, further 0.9-1.1 MPa.
[0022] Optionally, the thickness of the titanium carbide thin film material is 2-800 μm, further 10-600 μm, further 20-50 μm, and further 30-40 μm.
[0023] Based on the same inventive concept, the present invention also provides a titanium carbide thin film material, which is prepared by the preparation method as described above.
[0024] Based on the same inventive concept, the present invention also provides a zinc ion hybrid capacitor, comprising a titanium carbide thin film material prepared by the preparation method described above.
[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The ultra-wrinkled titanium carbide film prepared by the nanosheet twisting strategy of the present invention has a lower tortuosity, can provide a more direct ion transmission channel, and can effectively improve the ion transmission efficiency. When it is used to construct an electrode, it can significantly improve the ionic conductivity and electrochemical performance of the electrode, meeting the needs of high mass loading applications. The prepared electrode exhibits excellent electrochemical performance under high mass loading conditions, including ultra-high surface capacitance and more than 93% cycle stability (at 46.2 mg cm -2 mass load after 10,000 cycles).
[0026] (2) The titanium carbide thin film material prepared by the present invention has a super-corrugated structure and strong mechanical stability. The constructed electrode can effectively maintain structural integrity under high-voltage conditions, and can avoid fracture and peeling during the packaging and cycling of the energy storage device, thereby improving the long-term cycle stability of the electrode and ensuring the consistent performance of the energy storage device during multiple charge and discharge cycles.
[0027] (3) This invention not only provides a new material option for the development of high energy density energy storage devices, but also broadens the potential prospects of titanium carbide materials in a variety of high mass load applications.
[0028] (4) The titanium carbide thin film material prepared by the present invention provides more possibilities for various high-mass load energy storage applications, including portable devices, medical implants and high-efficiency chip design.
[0029] (5) The preparation process of the present invention is short and easy to implement, and can be conveniently promoted and applied in industrialization.
[0030] (6) The titanium carbide thin film material of the present invention can be used as a self-supporting electrode material and can be directly used as a positive electrode without the need for a binder, a conductive agent, and a current collector. This helps to further reduce the use of components that do not contribute to capacity, and also helps to simplify the electrode preparation process, making the electrode more green and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 is a SEM image of the titanium carbide aerogel material obtained by freeze drying, wherein: Figure 1 A SEM image of the titanium carbide aerogel material prepared in Example 1, Figure 1 B is the SEM image of pure titanium carbide aerogel powder.
[0032] Figure 2 : is a SEM image of the titanium carbide film and the pure titanium carbide film prepared in Example 1, wherein: Figure 2 A is a top view of the titanium carbide film prepared in Example 1, Figure 2 B is a cross-sectional view of the titanium carbide film prepared in Example 1, Figure 2 C is the top view of pure titanium carbide film. Figure 2 D is the cross-sectional view of pure titanium carbide film.
[0033] Figure 3 The titanium carbide film prepared in Example 1 is applied to a zinc ion hybrid capacitor, and a diagram of the rate performance of the zinc ion hybrid capacitor.
[0034] Figure 4 This is a diagram showing the electrochemical performance of the titanium carbide film prepared in Example 1 when applied to a zinc ion hybrid capacitor under high load.
[0035] Figure 5The titanium carbide film prepared in Example 1 is applied to a zinc ion hybrid capacitor, and a graph showing the cycle performance of the zinc ion hybrid capacitor.
[0036] Figure 6 The high-load titanium carbide film prepared in Example 1 is applied to a zinc ion hybrid capacitor, and a graph showing the cycle performance of the zinc ion hybrid capacitor.
[0037] Figure 7 These are digital photos of the titanium carbide film prepared in Example 1 before and after being loaded with weights.
[0038] Figure 8 This is the electrochemical impedance spectrum of the zinc ion hybrid capacitor assembled with the super-corrugated titanium carbide film prepared in Example 1.
[0039] Fig. 9 This is the electrochemical impedance spectrum of the zinc ion hybrid capacitor assembled with pure titanium carbide film.
[0040] Fig.10 This is a top view of the titanium carbide film of Comparative Example 3.
[0041] Fig.11 This is a top view of the titanium carbide film of Comparative Example 4. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0043] Example 1 Add 1 g of Ti3AlC2 to 10 mL of hydrofluoric acid solution (30 wt%), keep the solution temperature at 35 ºC, react for 6 hours, and then centrifuge and wash with deionized water until the pH value of the supernatant is 5-6 to obtain titanium carbide nanosheets. Then, the titanium carbide nanosheets were redispersed in 50 mL of a 15wt% aqueous solution of tetramethylammonium hydroxide, treated with water bath ultrasound for 1 hour (ultrasonic power of 300W), and then centrifuged at 3500 rpm for 1 hour, and the upper layer of liquid was taken to obtain intercalated titanium carbide nanosheet colloid (yield of 70wt%). Next, 5 mL of zinc sulfate solution (2 mol / L) was added dropwise to 20 mL of titanium carbide nanosheet colloid, stirred at room temperature for 10 minutes, and then centrifuged with deionized water to remove excess zinc sulfate. Then, the substrate obtained by centrifugation was freeze-dried to obtain a titanium carbide aerogel material (see Figure 1 A). Finally, the obtained titanium carbide aerogel was cold pressed into a film under a pressure of 1 MPa to obtain a titanium carbide film material with a super-wrinkled structure.
[0044] Zinc ion hybrid capacitors were assembled, in which the prepared film material was used directly as the positive electrode. Zinc ion hybrid capacitors were assembled in a button cell configuration with zinc foil as the negative electrode. Glass microfiber membrane was used as the separator. The electrolyte was a 2.5M zinc trifluoromethanesulfonate (Zn(OTF)2) aqueous solution.
[0045] from Figure 1 It can be seen that both the pure titanium carbide aerogel powder (omitting the zinc sulfate solution treatment step, specifically, directly freeze-drying the titanium carbide nanosheet colloid to obtain the titanium carbide aerogel material) and the super-wrinkled aerogel powder exhibit a porous structure, which is formed by the sublimation of ice during the freeze-drying process. The difference is that the super-wrinkled titanium carbide aerogel powder has a large number of wrinkled structures.
[0046] from Figure 2 It can be seen that compared with the pure titanium carbide film (the above-mentioned pure titanium carbide aerogel material is cold pressed into a film under a pressure of 1 MPa), the prepared titanium carbide film material with super-wrinkled structure has an obvious wrinkled porous structure. The pure titanium carbide film obtained under the action of pressure has a densely stacked structure and the pore structure completely disappears.
[0047] from Figure 3 It can be seen that compared with the pure titanium carbide film, the electrochemical performance of the zinc ion hybrid capacitor assembled with the titanium carbide film material prepared in Example 1 is significantly enhanced. -1 At a current density of 2.5 %, a specific capacitance retention rate of 51% can still be achieved, while the zinc ion hybrid capacitor assembled with pure titanium carbide film can only achieve a specific capacitance retention rate of 4%.
[0048] from Figure 4 It can be seen that the area specific capacitance (surface capacitance) of the zinc ion hybrid capacitor assembled with the super-wrinkled titanium carbide film material changes linearly with the increase of the load, and can reach up to 10.9 F cm -2 . Figure 5 It can be seen that the zinc ion hybrid capacitor assembled with the titanium carbide film material prepared in Example 1 exhibits very excellent cycle performance. -1 The current density can maintain more than 99% of the specific capacitance after more than 65,000 cycles, which greatly exceeds the cycle performance of commercial energy storage devices currently on the market. Figure 6 It can be seen that the zinc ion hybrid capacitor assembled with the titanium carbide film material prepared in Example 1 can still achieve excellent cycle performance even under high mass loading conditions. -2 The specific capacitance was retained over 93% after 10,000 cycles under load.
[0049] Among them, the constant current charge and discharge test was carried out in the potential range of 0.1-1.1 V (relative to Zn 2+ / Zn) and was completed using a NEWARE battery tester (model CT-4008T).
[0050] See also Figure 7 The morphology of the obtained ultra-wrinkled titanium carbide film did not change significantly before and after being loaded with weights, indicating that it has strong mechanical stability.
[0051] The tortuosity test was performed using a symmetrical cell, which included two electrodes of the same type (i.e., ultra-corrugated titanium carbide film or pure titanium carbide film) and a separator (model: GF / D, manufacturer: Whatman) sandwiched between the two electrodes. In addition, impedance spectroscopy tests (model: CHI660, manufacturer: Chenhua) were also performed on these symmetrical cells to determine the ionic impedance (R ion ). The tortuosity (τ) can be calculated by the following equation:
[0052] Where ε represents the porosity of the electrode, A is the area of the electrode, and k int is the intrinsic conductivity of the electrolyte (2.5 M aqueous zinc trifluoromethanesulfonate solution), and L represents the thickness of the electrode (the thickness of the super-wrinkled titanium carbide film is 394.4 μm, and the thickness of the pure titanium carbide film is 215 μm).
[0053] like Figure 8 and Fig. 9 As shown in the figure, the tortuosity of the super-wrinkled titanium carbide film is calculated to be 2.2, while the tortuosity of the pure titanium carbide film is calculated to be 15.7. The area of the electrode is controlled to be 0.25 cm 2 , the conductivity of the electrolyte was measured to be 5.08S / m. It can be seen from this that the super-corrugated structure prepared by the present invention effectively reduces the tortuosity of the electrode and greatly improves its dynamic performance.
[0054] Comparative Example 1 Example 1 was repeated, except that the concentration of the aqueous solution of tetramethylammonium hydroxide was 1 wt %.
[0055] As a result, the yield of intercalated titanium carbide nanosheet colloid decreased significantly, from 70 wt % to 40 wt %.
[0056] Comparative Example 2 Example 1 was repeated, except that the concentration of the aqueous solution of tetramethylammonium hydroxide was 50 wt %.
[0057] As a result, the yield of intercalated titanium carbide nanosheet colloid decreased significantly, from 70 wt % to 50 wt %.
[0058] Comparative Example 3 Example 1 was repeated, except that a 2M LiCl aqueous solution was used instead of a tetramethylammonium hydroxide aqueous solution.
[0059] Results, see Fig.10 , no obvious super-wrinkled porous structure appeared. The possible reason is that the ionic radius of lithium ions and zinc ions is similar, and the interlayer spacing of titanium carbide nanosheets will not change significantly during the ion exchange process, so the titanium carbide nanosheets will not be distorted. During the encapsulation process, the nanosheets form a tightly stacked film structure under the action of pressure.
[0060] Comparative Example 4 Example 1 was repeated, except that the amount of zinc sulfate solution added was 1 mL.
[0061] Results, see Fig.11 , the pore structure of the film is not well developed, and under the pressure of packaging, structural collapse occurs in some areas. The possible reason is that the amount of zinc ions added is not enough to distort all the titanium carbide nanosheets.
[0062] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.
Claims
1. A method for preparing a titanium carbide thin film material, characterized in that: The steps include: S1, providing titanium carbide nanosheets; S2, mixing the titanium carbide nanosheets and the aqueous solution of ammonium salt, ultrasonically treating, and then separating the solid and liquid, and taking the upper layer of liquid to obtain intercalated titanium carbide nanocolloids; Wherein, the ammonium salt is one or more of tetramethylammonium hydroxide, tetraethylammonium hydroxide, and tetrapropylammonium hydroxide; S3, adding a water-soluble salt to the intercalated titanium carbide nano-colloid, and after the reaction, performing solid-liquid separation, washing with water, and drying to obtain titanium carbide aerogel; Wherein, the water-soluble salt is one or more of zinc salt, sodium salt, lithium salt, potassium salt, magnesium salt, iron salt and calcium salt; S4, compression molding the titanium carbide aerogel to obtain a titanium carbide thin film material.
2. The preparation method according to claim 1, characterized in that: The preparation method of the titanium carbide nanosheets comprises the following steps: adding Ti3AlC2 into a hydrofluoric acid solution, maintaining the solution temperature at 25-40°C, reacting for 4-8 hours, centrifugally washing with deionized water until the pH value of the supernatant is 5-6, and obtaining titanium carbide nanosheets; wherein the concentration of the hydrofluoric acid solution is 20-40wt%.
3. The preparation method according to claim 1, characterized in that: In S2, the concentration of ammonium salt in the aqueous solution is 5-25wt%.
4. The preparation method according to claim 1, characterized in that: In S2, the ultrasonic treatment time is 30-90 min; during solid-liquid separation, centrifugation is performed at a rate of 3000-4000 r / min for 30-90 min.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In S3, an aqueous solution of a water-soluble salt is added dropwise to the intercalated titanium carbide nanocolloid, stirred for 5-45 minutes, washed by centrifugation with deionized water, and dried to obtain a titanium carbide aerogel; The concentration of the water-soluble salt in the aqueous solution of the water-soluble salt is 1.5-2.5 mol / L, and the amount of the aqueous solution of the water-soluble salt added is 0.2-0.3 times the volume of the titanium carbide nano-colloid.
6. The preparation method according to any one of claims 1 to 4, characterized in that: In S3, the drying method is freeze drying.
7. The preparation method according to any one of claims 1 to 4, characterized in that: In S4, the compression molding method is cold compression molding, and the molding pressure is 0.8-1.2 MPa.
8. The preparation method according to any one of claims 1 to 4, characterized in that: The thickness of the titanium carbide film material is 2-800 μm.
9. A titanium carbide thin film material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. A zinc ion hybrid capacitor, characterized in that: The invention comprises a titanium carbide thin film material prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method of preparing flexible bendable thin film electrode of supercapacitor
CN104992853A
A method for prepare a nitrogen doped carbon nanotube three-dimensional composite material by in-situ growth of a small lay of titanium carbide
CN109167066A
MXene composite gel material, and preparation method and application thereof
CN111269516A
Preparation method of one-dimensional titanium carbide nano roll
CN111573676A
Preparation method of 3D porous Sb / Ti3C2 MXene composite material for high-performance potassium ion battery
CN111710862A
Cited By
A sponge-hydrogel nanocomposite, a preparation method and application thereof
CN122771465A